Pure Bladder Malignant Rhabdoid Tumor Successfully Treated With Partial Cystectomy, Radiation, and Chemotherapy: A Case Report and Review of the Literature. Issue 8 (November 2021) - Assadi, Akram; Alzubaidi, Ahmad; Lesmana, Harry; Brennan, Rachel C.; Saad, Ali; Ortiz-Hernández, Vanessa; Gleason, Joseph M.
Abstract : Background: Extracranial pure malignant rhabdoid tumors (MRT) are aggressive tumors that carry a poor prognosis. Bladder MRTs are very rare and only 8 cases have been reported previously. Observation: We present a case of a child with bladder MRT. Despite the aggressive nature of the bladder tumor, it was successfully treated with bladder-sparing surgery, adjuvant radiotherapy, and chemotherapy. Conclusions: Our case, and review of 8 previously reported cases, suggests that bladder MRT seems to behave less aggressively when compared with other extracranial MRTs, and bladder preserving surgery should be considered when feasible.